MRI of plaque characteristics and relationship with downstream perfusion and cerebral infarction in patients with symptomatic middle cerebral artery stenosis. Issue 1 (30th October 2017) - Lu, Shan‐Shan; Ge, Song; Su, Chun‐Qiu; Xie, Jun; Mao, Jian; Shi, Hai‐Bin; Hong, Xun‐Ning
Abstract : Background: Intracranial plaque characteristics are associated with stroke events. Differences in plaque features may explain the disconnect between stenosis severity and the presence of ischemic stroke. Purpose: To investigate the relationship between plaque characteristics and downstream perfusion changes, and their contribution to the occurrence of cerebral infarction beyond luminal stenosis. Study Type: Case control. Subjects: Forty‐six patients with symptomatic middle cerebral artery (MCA) stenosis (with acute cerebral infarction, n = 30; without acute cerebral infarction, n = 16). Field Strength/Sequence: 3.0T with 3D turbo spin echo sequence (3D‐SPACE). Assessment: Luminal stenosis grade, plaque features including lesion T2 and T1 hyperintense components, plaque enhancement grade, and plaque distribution were assessed. Brain perfusion was evaluated on mean transient time maps based on the Alberta Stroke Program Early CT score (MTT‐ASPECTS). Statistical Tests: Plaque features, grade of luminal stenosis, and MTT‐ASPECTS were compared between two groups. The association between plaque features and MTT‐ASPECTS were assessed using Spearman's correlation analysis. Multivariate logistic regression and receiver operating characteristic (ROC) curves were constructed to assess the effect of significant variables alone and their combination in determining the occurrence of cerebral infarction. Results: Stronger enhanced plaques were associated with downstream lower MTT‐ASPECTS ( P = 0.010). Plaque enhancement grade ( P = 0.039, odds ratio [OR] 5.9, 95% confidence interval [CI] 1.1–32) and MTT‐ASPECTS ( P = 0.003, OR 2.6, 95% CI 1.4–4.7) were associated with a recent cerebral infarction, whereas luminal stenosis grade was not ( P = 0.128). The combination of MTT‐ASPECTS and plaque enhancement grade provided incremental information beyond luminal stenosis grade alone. The area under the receiver operating characteristic curve (AUC) improved from 0.535 to 0.921 ( P < 0.05). Data Concusion: Strongly enhanced plaques are associated with a higher likelihood of downstream perfusion impairment. Plaque enhancement and perfusion evaluation may play a complementary role to luminal stenosis in determining the occurrence of acute cerebral infarction. Level of Evidence: 4 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2017.